2009
DOI: 10.1111/j.1365-2648.2008.04954.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting with a diagnosis bipolar disorder

Abstract: The challenge for people working with parents who have been diagnosed with a bipolar disorder is to support them to feel confident in the management of their bipolar disorder and their ability to parent effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…A small qualitative literature has considered the subjective experiences of people diagnosed with BD, though stigma is more often a theme within, rather than a focus of, such research (J€ onsson et al, 2008;Lim et al, 2004;Michalak et al, 2006;Proudfoot et al, 2009;Sajatovic et al, 2008;Wilson and Crowe, 2008). Stigma is usually mentioned with respect to disclosure decisions (J€ onsson et al, 2008;Michalak et al, 2011Michalak et al, , 2007Proudfoot et al, 2009;Wilson and Crowe, 2008), though reported stigma experiences include stereotype application, distress, frustration and isolation within family, friendship, community, healthcare and employment contexts (Lim et al, 2004;Michalak et al, 2007;Proudfoot et al, 2009).…”
Section: Stigma and Bdmentioning
confidence: 96%
See 1 more Smart Citation
“…A small qualitative literature has considered the subjective experiences of people diagnosed with BD, though stigma is more often a theme within, rather than a focus of, such research (J€ onsson et al, 2008;Lim et al, 2004;Michalak et al, 2006;Proudfoot et al, 2009;Sajatovic et al, 2008;Wilson and Crowe, 2008). Stigma is usually mentioned with respect to disclosure decisions (J€ onsson et al, 2008;Michalak et al, 2011Michalak et al, , 2007Proudfoot et al, 2009;Wilson and Crowe, 2008), though reported stigma experiences include stereotype application, distress, frustration and isolation within family, friendship, community, healthcare and employment contexts (Lim et al, 2004;Michalak et al, 2007;Proudfoot et al, 2009).…”
Section: Stigma and Bdmentioning
confidence: 96%
“…Stigma is usually mentioned with respect to disclosure decisions (J€ onsson et al, 2008;Michalak et al, 2011Michalak et al, , 2007Proudfoot et al, 2009;Wilson and Crowe, 2008), though reported stigma experiences include stereotype application, distress, frustration and isolation within family, friendship, community, healthcare and employment contexts (Lim et al, 2004;Michalak et al, 2007;Proudfoot et al, 2009).…”
Section: Stigma and Bdmentioning
confidence: 97%
“…A significant proportion of individuals with serious mental illness have been shown to be concerned about their children’s risks for mood disorders (Austin et al, 2006; Quaid et al, 2001). These concerns appear to be related to worries about genetic predisposition along with perceived negative effects of their mental illness on parenting quality, family functioning and home stability (Austin et al, 2006; Calam et al, 2012; Hirschfeld et al, 2003; Wilson & Crowe, 2009). In a systematic review of qualitative studies exploring mothering with severe mental illness, Dolman and colleagues identified recurring themes (Dolman et al, 2013) related to affected mothers’ perceptions and needs.…”
Section: Introductionmentioning
confidence: 99%
“…Oyserman and colleagues (Oyserman et al, 2000) and Montgomery and colleagues (Montgomery et al, 2006) present critical reviews of literature in which affected parents are described in terms of the risk they pose to their children. This focus on pathology and risk is described by Wilson and Crowe (Wilson & Crowe, 2009) as reinforcing “inadequacy, fear, and dire predictions for their own and their children’s futures” for parents with BPD. Investigation is needed into effective ways that parents manage their cognitions and affect surrounding risks to their children.…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative evidence presents emic perspectives from two groups: mothers and mental health service providers. From a maternal orientation, key findings include acknowledgement of role complexity, desire to minimize negative and optimize positive familial and individual outcomes, and identification of the need for significant trusted other [2837]. A few studies present the perspective of those committed to servicing parents with SMI [3841].…”
Section: Introductionmentioning
confidence: 99%